Development of Social Economic Education Materials through Powerpoint - Yanto Bandje; Wa Ode Eli; Azan; Irman Matje; Jufri Agus (Termasyhur: Jurnal Pengabdian Masyarakat, 2025)
Socio-economic education plays an important role in shaping students' understanding of social realities and economic dynamics in society. However, learning is often still conventional, making it less interesting and less maximizing the potential of students. This activity aims to develop socio-economic learning materials by utilizing PowerPoint media as an interactive and interesting visual aid. The activity method used is a development approach through several stages, namely: needs analysis, material planning, PowerPoint media design, limited trials, and evaluation of results. This activity was carried out in an elementary school involving teachers and fifth grade students as trial subjects. The results of the activity showed that the use of PowerPoint was able to increase students' interest in learning, understanding of the material, and active participation in the learning process. The material presented in the form of visuals, animations, and systematic flows proved to be easier for students to understand than the usual lecture method. In conclusion, the development of socio-economic education materials through PowerPoint is an effective innovation in improving the quality of learning, and can be used as an alternative teaching media that is in accordance with current learning needs.